2018
DOI: 10.1038/s41419-018-0733-4
|View full text |Cite
|
Sign up to set email alerts
|

Proscillaridin A induces apoptosis and suppresses non-small-cell lung cancer tumor growth via calcium-induced DR4 upregulation

Abstract: Non-small-cell lung cancer (NSCLC) is the predominant histological type of lung cancer and is characterized by the highest mortality and incidence rates among these types of malignancies. Cardiac glycosides, a class of natural products, have been identified as a potential type of chemotherapeutic agent. This study aims to investigate the anti-cancer effects and the mechanisms of action of Proscillaridin A (P.A) in NSCLC cells. In vitro sodium–potassium pump (Na+/K+ ATPase) enzyme assays indicated that P.A is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 53 publications
2
27
1
Order By: Relevance
“…This discrepancy may result from the large differences with regard to the drug concentration and cellular contexts in the two studies, given that CGs are well known to initiate diverse signaling and biological effects at various concentrations in many cell types. Consistent with our data, other compounds in the CGs family, such as proscillaridin A, bufalin, and digitoxin, have been reported to induce AMPK activation at the nanomolar level in either cancer cell lines or normal human foreskin fibroblast cells, contributing to apoptosis or autophagy [ 26 29 ]. Interestingly, AMPK activation by proscillaridin A has been suggested to be correlated with the elevation of the intracellular Ca 2+ level, as the interruption of the NKA pump activity by CGs normally stimulates Na + /Ca 2+ exchange, leading to an increase in the calcium ion level [ 26 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This discrepancy may result from the large differences with regard to the drug concentration and cellular contexts in the two studies, given that CGs are well known to initiate diverse signaling and biological effects at various concentrations in many cell types. Consistent with our data, other compounds in the CGs family, such as proscillaridin A, bufalin, and digitoxin, have been reported to induce AMPK activation at the nanomolar level in either cancer cell lines or normal human foreskin fibroblast cells, contributing to apoptosis or autophagy [ 26 29 ]. Interestingly, AMPK activation by proscillaridin A has been suggested to be correlated with the elevation of the intracellular Ca 2+ level, as the interruption of the NKA pump activity by CGs normally stimulates Na + /Ca 2+ exchange, leading to an increase in the calcium ion level [ 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our data, other compounds in the CGs family, such as proscillaridin A, bufalin, and digitoxin, have been reported to induce AMPK activation at the nanomolar level in either cancer cell lines or normal human foreskin fibroblast cells, contributing to apoptosis or autophagy [ 26 29 ]. Interestingly, AMPK activation by proscillaridin A has been suggested to be correlated with the elevation of the intracellular Ca 2+ level, as the interruption of the NKA pump activity by CGs normally stimulates Na + /Ca 2+ exchange, leading to an increase in the calcium ion level [ 26 ]. The increased Ca 2+ concentration can consequently stimulate calmodulin-dependent kinase kinase β, which is another positive upstream regulator of AMPK [ 12 ].…”
Section: Discussionsupporting
confidence: 90%
“…These bacteria may shed different microbial bioactive molecules and affect the host ( 69 ). It is known that apoptosis is highly regulated and plays an important role in immune response and tumorigenesis ( 70 , 71 ). The p53 signaling pathway is recognized as a potential risk factor in lung adenocarcinoma tumorigenesis and survival ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…As indicated in Figure 3C , we noticed significant decrease in MMP in both MCF-7 and MDA-MB-231 cells. In previous studies, it has been shown that PSD-A increases intracellular Ca +2 level ( Li et al., 2018 ). Therefore, we determined the effect of PSD-A in MCF-7 and MDA-MB-231 cells by using Fluo-3AM.…”
Section: Resultsmentioning
confidence: 98%